Management effectiveness of large pelagic fisheries in the high seas. Issue 2 (30th November 2017) - Pons, Maite; Melnychuk, Michael C; Hilborn, Ray
Abstract: Large pelagic fishes are assessed and managed by tuna Regional Fisheries Management Organizations (tRFMOs). These organizations have been criticized for not meeting conservation objectives, which may relate to aspects of governance and management. No previous studies have systematically evaluated why management performance differs among tRFMOs and among stocks within each tRFMO. In this study, we collected data on the nature of research, management, enforcement and socioeconomics of management systems in the five principal tRFMOs of the world's oceans. We quantified influences of economic and fishery‐related factors on these management characteristics and examined how these factors vary among tRFMOs. We found that tRFMOs with a greater number of member countries, a greater economic dependency on tuna resources, a lower mean per capita gross domestic product, a greater number of fishing vessels and smaller vessels were associated with less intensive research, management and enforcement in these tuna fisheries. We also quantified the influence of specific management attributes and of biological, economic and fishery‐related factors on the trends and current status of large pelagic fish stocks in these regions. The most important factors correlated with trends and current stock status were external to the management systems, and included stock size, age at maturity, ex‐vessel price and economic dependency of countries on tuna fisheries. To improve the overall status of large pelagic fish stocks in the global high seas, more intensive data collection, research and management are needed in certain areas, especially in the Indian Ocean, and for certain stocks, especially non‐target species.